Entrepreneurial Activity for Integrating Mathematics, Art, and Social Science into Society - Arini Parhusip, Hanna; Dwi Purnomo, Hindriyanto; Budi Nugroho, Didit; Saptuti Kawuryan, Istiarsih (KnE Social Sciences, 2022)
This article shows how entrepreneurial activity is used in a mathematical research product. The used methods are online and offline marketing activities where mathematical formulas are implemented to create visual images, both 2-dimensional and 3-dimensional, namely parametric curves mapped with complex functions and using algebraic surfaces. The results of these activities are motifs built into the form of souvenirs, ornaments, accessories, and batik motifs. Furthermore, entrepreneurial activities were carried out with students, and small business craftsmen collaborated. The main result of this activity is the integration of mathematics with social and humanities activities. This has implications for the development of science and collaboration in economic recovery. Additionally, this activity provides production opportunities and provides new insights for ordinary people that mathematics can be expressed in batik motifs, accessories, souvenirs, and various derivative products. Keywords: entrepreneur; mathematics; parametric; algebraic surfaces